2010
DOI: 10.1111/j.1468-3083.2009.03562.x
|View full text |Cite
|
Sign up to set email alerts
|

What are the best outcome measures for assessing plaque psoriasis severity? A systematic review of the literature

Abstract: Based on this systematic review, it appears that none of the severity scores used for psoriasis meets all of the validation criteria required for an ideal score. However, we can conclude that the PASI score is the most extensively studied psoriasis clinical severity score and the most thoroughly validated according to methodological validation criteria. Despite certain limitations, use of the PASI score can be recommended for scientific evaluation of the clinical severity of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
197
0
16

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(222 citation statements)
references
References 38 publications
3
197
0
16
Order By: Relevance
“…A systemic review performed by Puzenat et al also showed that inter-rater variation was unacceptably high for the BSA. 6 For this reason, the BSA was not recommended for assessment of the clinical severity of psoriasis. The BSA could be calculated either by the "rule of nines" method or by the number of patient's hand areas affected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A systemic review performed by Puzenat et al also showed that inter-rater variation was unacceptably high for the BSA. 6 For this reason, the BSA was not recommended for assessment of the clinical severity of psoriasis. The BSA could be calculated either by the "rule of nines" method or by the number of patient's hand areas affected.…”
Section: Resultsmentioning
confidence: 99%
“…While these scales are commonly used to assess psoriasis severity in both clinical research and clinical practice, they have not been fully evaluated in terms of their validity and reliability, and no consensus exists on the best way to monitor psoriasis severity. 6,8 Despite its widespread use, the PASI has never been formally validated. Its grading has never been properly defined or standardized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Komponenty PASI ocenia się w 5-punktowej skali. Wskaźnik PASI stosuje się aktualnie jako złoty standard w ocenie stopnia nasilenia łuszczycy w badaniach klinicznych [20]. Obniżenie PASI o 75%, a nawet o 50% uznaje się za klinicznie istotne [21].…”
unclassified
“…PASI is a five-point scoring system that has become the gold standard in the assessment of the severity of psoriasis in clinical trials [20]. A reduction in PASI by 75% or even 50% is considered clinically significant [21].…”
mentioning
confidence: 99%